Development of high-performance anode/electrolyte/cathode micro-tubular solid oxide fuel cell via phase inversion-based co-extrusion/ co-sintering technique - Ab Rahman, Mazlinda; Othman, Mohd Hafiz Dzarfan; Fansuri, Hamzah; Harun, Zawati; Omar, Ahmad Faiq; Shabri, Hazrul Adzfar; Ravi, Jeganes; A Rahman, Mukhlis; Jaafar, Juhana; Ismail, Ahmad Fauzi; Osman, Nafisah (Elsevier, 2020)
A complete set of triple-layer (anode/electrolyte/cathode) hollow fiber for high temperature micro-tubular solid oxide fuel cell (MT-SOFC) consisting of nickel oxide (NiO) – yttria-stabilized zirconia (YSZ)/YSZ/lanthanum strontium manganite (LSM) – YSZ has been successfully fabricated in this study. A simplified fabrication technique of phase inversion-based co-extrusion/co-sintering has yielded a perfectly bounded sandwich structure with free-delamination and defect layers. The effect of co-sintering temperatures (1300 °C–1450 °C) on the morphologies, elemental distributions, electrolyte gas-tightness, mechanical strength, electrochemical performance and the impedance spectra test are well-inspected. The increase of co-sintering temperature has significant effects on the anode finger-like micro-channels shrinkage where the voids become very sharp-thin structure; and developing a thin gas-tight electrolyte layer. Whereas, rapid co-sintering rate (10 °C min -¹) and large particle size of 3–5 μm (micron) of YSZ has hindered the formation of fully dense cathode layer resulting from higher co-sintering temperature. Correspondingly, with only 0.1116 Ωcm2 value of area-specific resistance (ASR), a maximum power density has increased from 0.34 W cm ² to 0.75 W cm ² with 1.05 V OCV at 700 °C when the co-sintering temperature ranging from 1400 °C to 1450 °C; which comparable with single-layer counterpart.